Tractatus Politicus dan Demokrasi: Risalah Model-model Rezim yang Rasional - Norbertus Jegalus; Yohanes Subani (Institut Filsafat dan Teknologi Kreatif Ledalero, 2023)
Abstract: Tractatus Politicus is a work of Spinoza's political philosophy which discusses regime models arranged in stages according to the level of use of reason: Monarchy is rational, aristocracy is more rational, and democracy is most rational. Spinoza, who is known as the prophet of reason, established rationality as a normative standard forthe three types of regimes. The rationality of a regime is measured by the size of the council which is tasked with discussing and controlling all state policies and Spinoza considers democracy to be the most rational because democracy allows for a people's council that is bigger than monarchy and aristocracy. Supomo adopted Spinoza's views as one of the philosophical sources for his state theory known as the